ESTUDO QUÍMICO DOS METABÓLITOS SECUNDÁRIOS DAS FOLHAS DE Calea hispida Baker - Name, Lorna Hosoya (2014)
This research work aimed to study, chemically, the leaves of Calea hispida Baker, Asteraceae, that grows in natura in the Second Plateau of Paraná State by assessing the potential bioactivity of its secondary metabolites. This research was carried out because this is a poorly studied plant species and due to the occurrence of several classes of bioactive compounds in plants of this genus, although this plant is not recognized as medicinal. The leaves were hydrodistilled, in triplicate, to obtain the essential oils and analyze their chemical composition by GC/MS/FID standard techniques. This was the first chemical study of the essential oil from C. hispida, allowing the identification of several oxygenated monoterpenes in low proportions, such as terpineol, cis-sabinol, verbenone, and bornylacetate, not oxygenated sesquiterpenes in individual percentages below 5.2%, such as cubebene, germacrene D, and -selinene, and oxygenated sesquiterpenes that totaled between 7.86 to 11.46% in the replicates, such as (E)-nerolidol, spathulenol, and viridiflorol. Additionally, three compounds containing an aromatic ring in their chemical structures totaled between 31.43 and 56.20% of essential oils: 2,6-dibutyl-4-methylphenol (0.39 to 1.44%), (Z)-3-hexenyl benzoate (0.40 to 0.43%), and a major compound found in proportions between 30.21 and 54.76% which could not be identified by GC/MS. The major volatile unidentified substance was isolated by fractionation of the essential oil by means of a chromatography column. Its chemical structure was assessed by UV-Vis, FT-IR, 1H and 13C NMR spectra, which allowed the identification of 6-acetyl-7-hydroxy-2,2-dimethylchromene. In parallel, the isolated chromene was provided for studies of its crystal structure by X-ray diffraction methods. Extractions with chloroform from aqueous solutions that remained after hydrodistillation of leaves aimed to remove less polar substances, so extracts containing phenolic compounds could be obtained. Thus, ethyl acetate and ethyl acetate/methanol 30% extracts were obtained at pH 8 to achieve extracts containing solid neutral phenolic substances, as well as at pH 4 (for acidic phenolic compounds). An ethyl acetate/methanol extract at pH 8 presented only one main phenolic substance which was identified as quercetin-3-O-rhamnopyranoside by analysis of its UV, FT-IR, and 1H and 13C NMR spectra. Preliminary analyzes of extracts obtained at pH 4 showed that the acidic phenolic compounds are an important class of substances in C. hispida, consisting mainly of caffeic acid derivatives, such as 3,5-dicaffeoylquinic and 4,5-dicaffeoylquinic. This work also allowed the determination of the bioactivity profile of the secondary metabolites from leaves of C. hispida by providing extracts and isolated compounds for biological tests, such as antioxidant capacity against DPPH radical, protection of leukocytes in a medium that causes lysis, and evaluation of fungitoxic, allelopathic, antimicrobial, and inhibitory acetylcholinesterase activities.